Bioequivalence Study of Three Ciclosporin Capsule Formulations in Healthy Volunteers - Chachad, Siddarth; Lulla, Amar; Malhotra, Geena; Purandare, Shrinivas (Arzneimittelforschung, 2009)
The study was conducted in order to assess the bioequivalence of three capsule formulations containing 100 mg of ciclosporin (CAS 59865-13-3). 24 Healthy volunteers, 20 to 37 years of age (mean 26, SD 5.3 years), weighing 51 to 76 kg (mean 65, SD 7.0 kg) and a body height of 1.5 to 1.83 m (mean 1.68, SD 0.07 m) were enrolled in the study. Each volunteer received a single oral dose of 300 mg (3 100 mg ciclosporin capsules) on three separate occasions according to a randomized, single-dose, three-way crossover design with three formulations of ciclosporin: Treatment I (reference formulation, capsules), Treatment II (test formulation 1, soft gel capsules), Treatment III (test formulation 2, hard gel capsules). Blood samples for the determination of ciclosporin were drawn at scheduled intervals up to 56 h after dosing. Ciclosporin concentrations in whole blood were determined by a specific HPLC method with ultraviolet detection. Quantitation of ciclosporin was validated for concentrations range from 25 to 1600 ng/ml. Since the 90% confidence intervals for the “test/reference” mean ratio of the Log-transformed pharmacokinetic variables Cmax, AUC0–t and AUC0–∞ were clearly within the bioequivalence range of 80% to 125%, the treatments were considered bioequivalent in terms of both the rate and extent of absorption.
Keywords: CAS 59865-13-3; Ciclosporin, pharmacokinetics, bioequivalence; Immunosuppressants